Confirmation for delivery of jet grouting equipment - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the confirmation for the delivery of jet grouting equipment of Brac University new campus development project .